The Cambridge Handbook of Corporate Law, Corporate Governance and Sustainability 2019
DOI: 10.1017/9781108658386.004
|View full text |Cite
|
Sign up to set email alerts
|

Corporations and Sustainability

Abstract: Corporations and sustainability BEATE SJÅFJELL AND CHRISTOPHER M. BRUNER * 1. Establishing the field of corporate law, corporate governance and sustainability * This chapter draws on research in the project Sustainable Market Actors for Responsible Trade (SMART).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In legal scholarship, “sustainability” has slowly evolved from a broad general concept to a narrower one, and an object to be promoted by law (Salminen and Rajavuori, 2021). Sjåfjell and Bruner (2020) have described sustainability as an overarching societal goal – a state in which all human activity must be directed toward respecting planetary boundaries, protecting human rights and meeting fundamental social needs. The concept of “planetary boundaries” has been used to illustrate the safe operating space for humanity (Rockström et al , 2009).…”
Section: Legal Perspective On Sustainability and Sustainable Supply C...mentioning
confidence: 99%
See 1 more Smart Citation
“…In legal scholarship, “sustainability” has slowly evolved from a broad general concept to a narrower one, and an object to be promoted by law (Salminen and Rajavuori, 2021). Sjåfjell and Bruner (2020) have described sustainability as an overarching societal goal – a state in which all human activity must be directed toward respecting planetary boundaries, protecting human rights and meeting fundamental social needs. The concept of “planetary boundaries” has been used to illustrate the safe operating space for humanity (Rockström et al , 2009).…”
Section: Legal Perspective On Sustainability and Sustainable Supply C...mentioning
confidence: 99%
“…They have argued that the major challenge of the 21st century is to secure the social foundations while ensuring that the overall pressure on Earth systems remains within planetary boundaries. Sjåfjell and Bruner (2020) have clarified that the social foundation is the minimum that humanity must strive for, while planetary boundaries represent the limits to how much pressure can be put on ecosystems to achieve this.…”
Section: Legal Perspective On Sustainability and Sustainable Supply C...mentioning
confidence: 99%
“…This may be contrasted to the general and multifaceted purpose of advancing social welfare (Aglietta & Rebérioux, 2005; Johnston, 2009; Sjåfjell, 2009). Shareholder primacy does not have a company law basis; rather it is a short form for a complex mix of perceived market signals and economic incentives, informed by path‐dependent corporate governance assumptions and postulates from U.S.‐based legal‐economic theories (Bruner, 2013; Sjåfjell & Bruner, 2019; Smith, 1988; Sneirson, 2019). This is evidenced through a decade of multijurisdictional comparative company law analysis, which has demonstrated that company laws across jurisdictions give boards as the core decision‐makers discretion to govern the companies in the way they see fit, and that this space is constrained by shareholder primacy (Ireland, 1999; Sjåfjell et al, 2015; Sjåfjell & Bruner, 2019; Stout, 2012, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Shareholder primacy does not have a company law basis; rather it is a short form for a complex mix of perceived market signals and economic incentives, informed by path‐dependent corporate governance assumptions and postulates from U.S.‐based legal‐economic theories (Bruner, 2013; Sjåfjell & Bruner, 2019; Smith, 1988; Sneirson, 2019). This is evidenced through a decade of multijurisdictional comparative company law analysis, which has demonstrated that company laws across jurisdictions give boards as the core decision‐makers discretion to govern the companies in the way they see fit, and that this space is constrained by shareholder primacy (Ireland, 1999; Sjåfjell et al, 2015; Sjåfjell & Bruner, 2019; Stout, 2012, 2013). Shareholder primacy has so far in aggregate proven to be stronger than competing norms, where the OECD Guidelines for Multinational Enterprises (OECD, 1976) and the UN Guiding Principles for Business and Human Rights (United Nations, 2011) are significant examples.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Corporate law and corporate governance set the regulatory structure for decision-making by companies, making it intertwined with the sustainability issues mentioned above. As a result, corporate law, corporate governance and sustainability are significant to be studied, considering the crises that have arisen globally (Sjåfjell and Bruner, 2019). Presently, the literature is lacking in deliberating the potential of corporate law and corporate governance to promote corporate sustainability by integrating non-financial factors into corporate law itself (Jebe et al , 2018; Monciardini et al , 2020).…”
Section: Introductionmentioning
confidence: 99%